Using Common Sense: A Linguistic Perspective on Judicial Interpretations of “Use a Firearm” - Clark D. Cunningham; Charles J. Fillmore (Washington University Law Quarterly, 1995)
This Article will show how analytical methods of legal and linguistic scholarship can interact to examine a legal text, in particular a provision of the federal criminal code, the interpretation of which has been hotly contested within the legal system.
Keywords: Linguistics; Law – Interpretation & amp; construction